Xenograft Models for Preclinical Assessment of Anticancer Therapies: A Comprehensive Review - Ebrahim sadaqa; Muhammad Ikhlas Arsul (Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction: Xenograft models play a pivotal role in preclinical studies for assessing the efficacy of anticancer medications. In this comprehensive review, we present an overview of current advancements and future prospects in xenograft research, focusing on their significance in guiding drug development and clinical translation. Aim: Our aim is to conduct an in-depth review of xenograft models, their utility in evaluating anticancer drug effectiveness and ultimately improve patient outcomes. Methods We conducted an in-depth literature search using databases such as ScienceDirect, Google Scholar and PubMed with keywords including